1986
DOI: 10.1080/09553008614551291
|View full text |Cite
|
Sign up to set email alerts
|

Radiosensitization by Cisplatin of RIF1 Tumour Cellsin Vitro

Abstract: The ability of cis-diamminedichloroplatinum (II) (c-DDP) to enhance radiation-induced cell killing was tested on oxic RIF1 tumour cells in monolayer culture. Marked radiosensitization of the survivors of a 1 h drug treatment was found with all c-DDP doses tested, with enhancement ratios increasing from 1.2 to 2.2 with increasing drug dose. Isobologram analyses showed that the interactions of c-DDP with X-rays were supra-additive. To test whether part of the enhancement was due to a selection of subpopulations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(25 citation statements)
references
References 19 publications
2
23
0
Order By: Relevance
“…Results from studies using exponentially growing cell cultures vary from a cisplatin-induced radiosensitisation (31)(32)(33)115), to a merely additive effect (29,31,(116)(117)(118). The effect of cisplatin treatment on radiosensitivity may depend on the cell type used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from studies using exponentially growing cell cultures vary from a cisplatin-induced radiosensitisation (31)(32)(33)115), to a merely additive effect (29,31,(116)(117)(118). The effect of cisplatin treatment on radiosensitivity may depend on the cell type used.…”
Section: Discussionmentioning
confidence: 99%
“…Cisplatin-based chemoradiotherapy has become standard treatment for, among others, locally advanced cervical carcinoma (30) and locally advanced non-small-cell lung cancer (NSCLC) (31). There have been numerous studies on the radiation-sensitising effect of cisplatin; however, the results vary from a clear cisplatin-induced radiosensitisation (24,25,(32)(33)(34) to a merely additive effect on cell survival (35). Cisplatin and radiation share a common cellular target, DNA (36).…”
Section: Cisplatinmentioning
confidence: 99%
“…There have been many studies on the radiation sensitizing effect of cisplatin, but results vary from a clear cisplatin-induced radiosensitization (Begg et al, 1986;Nakamoto et al, 1996;Bergs et al, 2006 to only an additive effect on cell survival (Fehlauer et al, 2000). Cisplatin and radiation have in common that their cellular target is DNA (Rabik & Dolan, 2007).…”
Section: Cisplatinmentioning
confidence: 99%
“…Later, cisplatin was found to inhibit sublethal radiation damage repair (SLDR) of human SCC line only when it was administered at the time of radiation (10). In addition, some investigators have reported inhibition of SLDR only in hypoxic tumors (32,34), while still others have found the same effect also in euoxic tumours (26). These controversial results deDend Dartlv on different ex-.…”
Section: Discussionmentioning
confidence: 94%
“…The first evidence of an actual interaction between cisplatin and radiation came from Zak & Drobnik in 1971 (25). A true radiosensitising effect of cisplatin on tumour cells has been reported occasionally in some animal tumours in vivo (26)(27)(28)(29)(30)(31) and in vitro (32). Some investigators, on the other hand, have not found any enhancement in vivo (33) or in vitro (8,9).…”
Section: Discussionmentioning
confidence: 97%